Warehouse management : The definitive guide to improving efficiency and minimizing costs in the modern warehouse - Richards, Gwynne (Kogan Page, 2022)
This book covers an extensive range of topics from defining the modern warehouse, detailing management processes, strategies, and practices to outlining how to tackle environmental challenges to ensure a sustainable supply chain.